2002
DOI: 10.1212/wnl.58.8.1182
|View full text |Cite
|
Sign up to set email alerts
|

Association between the APOE genotype and psychopathologic symptoms in Alzheimer’s disease

Abstract: Background-Psychiatric symptoms occur frequently in the course of AD, are a frequent contributor to institutionalization, predict cognitive decline and death, and often require treatment with psychotropic medications. Previous studies investigating the association between APOE genotype and psychiatric symptomatology in AD have reported contradictory results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
94
1
2

Year Published

2006
2006
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(106 citation statements)
references
References 66 publications
(84 reference statements)
9
94
1
2
Order By: Relevance
“…Fifteen studies (including the present one) have examined psychotic symptoms, and six (including the present one) have reported that e4 increased the risk for psychosis (Ramachandran et al, 1996;Ballard et al, 1997;Harwood et al, 1999;Weiner et al, 1999;Scarmeas et al, 2002), whereas nine have found no effect of e4 (Lehtovirta et al, 1996a;Cacabelos et al, 1997;Lopez et al, 1997;Lyketsos et al, 1997;Hirono et al, 1998Hirono et al, , 1999Levy et al, 1999;Gabryelewicz et al, 2002;Sweet et al, 2002). Among the six positive studies only two others (Weiner et al, 1999;Scarmeas et al, 2002) have considered delusions and hallucinations separately. Our exploratory finding that e4 was preferentially associated with delusions was shared by Scarmeas et al (2002) who observed that e4 was associated specifically with an increased risk for delusions in a dose dependent manner, whereas e4 homozygotes actually had a reduced risk for hallucinations.…”
Section: Comparison To Other Apoe E4 Ad Psychosis Studiesmentioning
confidence: 68%
See 4 more Smart Citations
“…Fifteen studies (including the present one) have examined psychotic symptoms, and six (including the present one) have reported that e4 increased the risk for psychosis (Ramachandran et al, 1996;Ballard et al, 1997;Harwood et al, 1999;Weiner et al, 1999;Scarmeas et al, 2002), whereas nine have found no effect of e4 (Lehtovirta et al, 1996a;Cacabelos et al, 1997;Lopez et al, 1997;Lyketsos et al, 1997;Hirono et al, 1998Hirono et al, , 1999Levy et al, 1999;Gabryelewicz et al, 2002;Sweet et al, 2002). Among the six positive studies only two others (Weiner et al, 1999;Scarmeas et al, 2002) have considered delusions and hallucinations separately. Our exploratory finding that e4 was preferentially associated with delusions was shared by Scarmeas et al (2002) who observed that e4 was associated specifically with an increased risk for delusions in a dose dependent manner, whereas e4 homozygotes actually had a reduced risk for hallucinations.…”
Section: Comparison To Other Apoe E4 Ad Psychosis Studiesmentioning
confidence: 68%
“…Among the six positive studies only two others (Weiner et al, 1999;Scarmeas et al, 2002) have considered delusions and hallucinations separately. Our exploratory finding that e4 was preferentially associated with delusions was shared by Scarmeas et al (2002) who observed that e4 was associated specifically with an increased risk for delusions in a dose dependent manner, whereas e4 homozygotes actually had a reduced risk for hallucinations. By contrast, Weiner et al (1999) reported marginal (P ¼ 0.05) positive associations between ApoE e4 and both delusions and hallucinations.…”
Section: Comparison To Other Apoe E4 Ad Psychosis Studiesmentioning
confidence: 99%
See 3 more Smart Citations